Pengaruh Program Pemutihan Pajak Kendaraan Bermotor, Pembebasan Bea Balik Nama Kendaraan Bermotor Dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Pusat Pengelolaan Pendapatan Wilayah (P3dw) Kabupaten Bandung I Rancaekek - Adella Mutiara Nurul Fitri; Rosyani Muthya (CV. ITTC INDONESIA, 2024)
This research aims to determine the magnitude of the influence of the tax whitening program, exemption from motor vehicle title transfer fees and tax socialization on taxpayer compliance at the Bandung I Rancaekek Regency Regional Revenue Management Center (P3DW). The method used in this research is a quantitative method with a descriptive and verificationapproach with the population taken, namely motor vehicle owners registered with Samsat Rancaekek in 2023. The sampling technique uses a probability sampling technique with the method simple random sampling. The data source in this research is primary data by distributing 202 questionnaires to meet the requirements. The results of this research show that the motor vehicle tax reduction program, exemption from motor vehicle title transfer fees, and tax socialization partially influence motor vehicle taxpayer compliance. Based on a simultaneous test (f test), this research shows that the motor vehicle tax reduction program, exemption from motor vehicle title transfer fees and tax socialization simultaneously influence motor vehicle taxpayer compliance. And based on the results of the coefficient of determination test (R2), it shows that the independent variable used in this research simultaneously contributed 62.8% to motor vehicle taxpayer compliance